Simultaneous Determination of Glibenclamide and Silymarin Released from Chitosan Microparticles by HPLC-ESI-MS Technique: Method Development and Validation - Mihaela-Iustina Condurache; Anca-Roxana Petrovici; Natalia Simionescu; Bianca-Stefania Profire; Luminita-Georgeta Confederat; Alexandra Bujor; Anca Miron; Lenuta Profire (MDPI AG, 2022)
The study aim was to develop and validate a high-performance liquid chromatography-electrospray ionization mass spectrometry (HPLC-ESI-MS) method to simultaneously determine glibenclamide (Gli) and silymarin (Sil) released from chitosan (CS) microparticles in aqueous solutions. The CS microparticles were synthesized using an ionic gelation method, and their morphology, swelling degree, encapsulation efficiency and active substance release were investigated. Gli and Sil were loaded in different concentrations, and their identification and quantification were performed using the HPLC-ESI-MS method, which was further validated. The drugs' characteristic m/z was found in the higher intensity of retention time (Rt) (Gli, 8.909 min; Sil A, 5.41 min; and Sil B, 5.66 min). The method selectivity and precision are very good, and the blank solution proved no interference. The linearity of the answer function is very good for Sil A (R2 = 1), Sil B (R2 = 0.9998) and Gli (R2 = 0.9991). For Gli, we obtained a limit of detection (LOD) = 0.038 mg/mL and limit of quantification (LOQ) = 1.275 mg/mL; for Sil A, a LOD = 0.285 mg/mL and LOQ = 0.95 mg/mL; and for Sil B, a LOD = 0.045 mg/mL and LOQ = 0.15 mg/mL. A high-resolution HPLC-ESI-MS method was developed and validated, which allowed the simultaneous determination of Gli and Sil loaded in CS microparticles, in a concentration range of 0.025-1 mg/mL.